MODERN SCIENTIFIC ANALYSIS OF RELATION OF ISLAM TO BLEPHAROPLASTY AS AESTHETIC PROCEDURE (International Educators Conference, 2025)
Plastic surgery, especially blepharoplasty, continues to attract attention both from the point of view of medicine and from the point of view of religious norms, including Islamic ones. This article examines the main aspects affecting the perception of blepharoplasty in Islamic societies, based on recent research. Special attention is paid to theological and legal aspects, as well as social and cultural factors influencing attitudes towards operations such as blepharoplasty. Islam considers interference in human nature through the prism of ethical norms established in the Qur'an and the hadith of the Prophet Muhammad صلى الله عليه وسلم (peace and blessings be upon him). The article also provides an appropriate interpretation of verses from the Koran and hadith relating to the change of appearance and the permissibility of procedures such as blepharoplasty within the framework of Islamic ethics and law.